Effect of a vitamin supplement and three species of food plants (Fabaceae) on the production of Morpho helenor butterflies (Nymphalidae:Lepidoptera) (UNED Research Journal, 2017)
Little has been published on the use of artificial diets for the production of butterflies in the Nymphalidae family. We evaluated the effect of a commercial vitamin supplement called Farvital - 18, composed of amino acids, vitamins and electrolytes, on the production of the butterfly Morpho helenor. This supplement was applied on three host plants from the family Fabaceae: Lonchocarpus oliganthus, Erythrina berteroana and Arachis pintoi. We analyzed the duration of the larval stages, the growth rate of the caterpillars at each stage, the survival rate of the caterpillars, pupal weight, and quality and quantity of pupae obtained. Lonchocarpus oliganthus without and with the addition of vitamin supplement produced larger caterpillars, higher survival rate, shorter larval stage duration, and produced heavier and better quality pupae. Arachis pintoi with and without vitamin supplement produced pupae of lower weight. Males fed on Lonchocarpus oliganthus hatched faster but for females the food did not make any difference. Independent of the diet used for the 600 initial larvae, 371 pupae were produced (61,83%). Of the total pupae obtained, 3,63% did not emerge and 88% of the pupae were A quality. The greatest adult emergence occurred between days 14 and 15 of the pupa formation. The pupae of females were heavier than males. The native plant Lonchocarpus oliganthus gave better yields in the production of butterflies Morpho helenor.
Keywords: Host plant; caterpillar; pupae; butterfly; Morpho helenor; lepidoptera; production butterflies; nutritional supplement